Effects of domestic worker legislation reform in Brazil - Joana Sim\~oes Costa; Ana Luiza Neves de Holanda Barbosa; Guilherme Issamu Hirata (International Policy Centre for Inclusive Growth (IPC-IG), 2016)
This study investigates the impact of the extensions of labour rights (as foreseen in Constitutional Amendment 72 of 2 April 2013) over the formalisation, working hours and wages of Brazilian domestic workers. We also aim to identify whether this new legislation has resulted in the shift of domestic workers to unemployment or other labour status. The methodology combines the difference-in-differences approach with propensity score reweighting. The analysis is carried out with microdata from the National Household Sample Survey (Pesquisa Nacional por Amostra de Domicílios - PNAD) from 2012 through 2014. Our results suggest that this legislation increased the number of formal jobs, reduced the amount of working hours and had no effect on the wages of monthly domestic workers. [...]
Keywords: J2; J38; J4; 330; domestic work; formal sector; working hours